Competences for environmental sustainability: a systematic review on the impact of absorptive capacity and capabilities - Dzhengiz, Tulin (Journal of business ethics, 2020)
Responsible management competences are the skills of managers to deal with the triple bottom line, stakeholder value and moral dilemmas. In this paper, we analyse how managers develop responsible management competences and how the competences interact with capabilities at the organisational level. The paper contributes to the responsible management literature by integrating research on absorptive capacity and organisational learning. By creating intersections between these disparate research streams, this study enables a better understanding of the development of responsible management competences. The paper is a systematic literature review on environmental competences, which are a type of responsible management competences referring to the managerial skills aimed at improving environmental sustainability. The findings demonstrate that managers who are able to recognize and acquire external knowledge develop environmental competences, and organisations capable of assimilating, transforming and exploiting knowledge develop environmental capabilities. The paper establishes that a dynamic and recursive relation exists between environmental competences and capabilities. Antecedents and contextual conditions specific to a sustainability context, such as eco-centric values and stakeholder pressures, influence the development of environmental competences. The study shows that environmental competences have a positive direct effect on environmental performance, and an indirect effect as a mediator between environmental capabilities and performance.